2018
DOI: 10.1038/s41598-018-20641-5
|View full text |Cite
|
Sign up to set email alerts
|

β-catenin-independent regulation of Wnt target genes by RoR2 and ATF2/ATF4 in colon cancer cells

Abstract: Wnt signaling is an evolutionarily conserved signaling route required for development and homeostasis. While canonical, β-catenin-dependent Wnt signaling is well studied and has been linked to many forms of cancer, much less is known about the role of non-canonical, β-catenin-independent Wnt signaling. Here, we aimed at identifying a β-catenin-independent Wnt target gene signature in order to understand the functional significance of non-canonical signaling in colon cancer cells. Gene expression profiling was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 73 publications
1
37
1
1
Order By: Relevance
“…The ROR2 protein is a transmembrane receptor for Wnt noncanonical pathway activation. Recent study revealed that the noncanonical Wnt target genes are dependent on ROR2 [ 46 ]. Lara et al also demonstrated that ROR2 is repressed by aberrant promoter of hypermethylation in CRC tissues [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…The ROR2 protein is a transmembrane receptor for Wnt noncanonical pathway activation. Recent study revealed that the noncanonical Wnt target genes are dependent on ROR2 [ 46 ]. Lara et al also demonstrated that ROR2 is repressed by aberrant promoter of hypermethylation in CRC tissues [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with this, FZD7 gene silencing reduces migration of WNT11-transfected HCT116 cells [6]. However, FZD7 gene silencing also reduces Wnt-β-catenin signaling [10] and FZD 7 is also a receptor for Wnt-3A [11,12], which increases CRC cell proliferation [13], and for Wnt-2B, which drives the mesenchymal to epithelial transition (MET) [14]. Moreover, FZD 8 transduces Wnt-11 signals that promote prostate cancer cell migration, invasion and the epithelial mesenchymal transition (EMT) [15].…”
Section: Introductionmentioning
confidence: 84%
“…Deregulation of the canonical Wnt pathway has been implicated in cancers, but the roles of the non-canonical Wnt pathway in cancers remain largely unexplored. Some reports suggest the tumour-promoting [ 55 , 56 ] or repressive [ 57 ] functions of non-canonical Wnt pathway in CRC development. Voloshanenko et al proposed that WNT5A/B (the non-canonical ligands) regulate the expression of non-canonical Wnt target genes, such as PLOD2 and HADH, which are necessary for the proliferation and viability of CRC cells [ 56 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some reports suggest the tumour-promoting [ 55 , 56 ] or repressive [ 57 ] functions of non-canonical Wnt pathway in CRC development. Voloshanenko et al proposed that WNT5A/B (the non-canonical ligands) regulate the expression of non-canonical Wnt target genes, such as PLOD2 and HADH, which are necessary for the proliferation and viability of CRC cells [ 56 ]. Recent work has also identified a direct role for WNT5A in promoting the migration and invasion of CRC cells [ 55 ].…”
Section: Introductionmentioning
confidence: 99%